Disfunctions of the System Human – Work in the Healthcare Entities - Pytel-Kopczyńska, Marzena (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Health and work determine each other. Work environment, the system human being – technical object – surrounding are the determinants of life quality including widely understood health. Situational factors connected with work such as work conditions, balance between work – family life, the possibility to regenerate your strengths, forms of work organization constitute an important prohealth factor. The work environment which is created in a wrong way may contribute to the increase in the stress level, occupational burnout and affect the security level. The subject literature presents numerous arguments confirming the necessity to promote health in the work place. The purpose of this study is to present the main topic area referring to the dysfunctions of the system human – work in respect to the employees of the healthcare under the empirical research.